2006
DOI: 10.1128/iai.74.2.994-1000.2006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Safety and Immunogenicity of Two Attenuated Enterotoxigenic Escherichia coli Vaccine Strains in Healthy Adults

Abstract: A vaccine against enterotoxigenic Escherichia coli (ETEC) is needed to prevent diarrheal illness among children in developing countries and at-risk travelers. Two live attenuated ETEC strains, PTL002 and PTL003, which express the ETEC colonization factor CFA/II, were evaluated for safety and immunogenicity. In a randomized, double-blind, placebo-controlled trial, 19 subjects ingested one dose, and 21 subjects ingested two doses (days 0 and 10) of PTL-002 or PTL-003 at 2 ؋ 10 9 CFU/dose. Anti-CFA/II mucosal imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Follow-up studies demonstrated that many of these proteins could be found in OMVs that provide protection against ETEC colonization in mice (789). Live attenuated vaccines expressing either CFA/I (ACAM2010), CFA/II (PTL-003), or a combination of CS1, CS2, and CS3 (ACAM2017) were first evaluated in phase 1 trials and resulted in an antibody response to their respective CFs (790)(791)(792). Follow-up studies with PTL-003-vaccinated human volunteers did not show adequate protection against ETEC-induced diarrhea (793).…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…Follow-up studies demonstrated that many of these proteins could be found in OMVs that provide protection against ETEC colonization in mice (789). Live attenuated vaccines expressing either CFA/I (ACAM2010), CFA/II (PTL-003), or a combination of CS1, CS2, and CS3 (ACAM2017) were first evaluated in phase 1 trials and resulted in an antibody response to their respective CFs (790)(791)(792). Follow-up studies with PTL-003-vaccinated human volunteers did not show adequate protection against ETEC-induced diarrhea (793).…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…Vaccine strains ACAM2022, ACAM2025, and ACAM2027 all express the LTB subunit and between them express CFA/I, CS1, CS2, CS3, CS5, and CS6. Precursors of ACAM2025 (ACAM2010) and ACAM2027 (ACAM2007 and ACAM2017) have already been demonstrated to be safe and immunogenic in human volunteers (5,31), as has PTL003, which was similarly attenuated (15,32).…”
Section: Discussionmentioning
confidence: 99%
“…This has the dual advantages of presenting newly synthesized antigens in their native conforma-tion to the immune system as the vaccine organisms colonize and undergo limited replication in the gastrointestinal tract as well as providing a large number of surface molecules, in addition to the known colonization factors which may additionally contribute to protection. It has previously been shown that live, toxin-negative ETEC derivatives that have had deletion mutations introduced into the aroC, ompC, and ompF genes, expressing CFA/I (5, 31) and CFA/II (5,15,32), are safe and immunogenic when administered orally to human volunteers. A vaccine containing strains expressing CFA/I, CFA/II, and CFA/IV plus LTB may provide protection against up to 90% of ETEC strains in most areas (23,35).…”
mentioning
confidence: 99%
“…The vaccine strain was administered to half of the volunteers by thawing these vials, diluting the strain in PBS to provide the desired dose of organisms in 1 ml of suspension, adding 1 ml to 200 ml of CeraVacx buffer (Cera Products Inc., Jessup, MD; rice solids, 7.0 g; sodium bicarbonate, 2 g; trisodium citrate, 0.5 g, in 200 ml of water), and having them drink it ("frozen vaccine"). To compare this vaccine with studies done previously (21,42), the remaining volunteers were given "fresh vaccine" in which a freshly prepared lawn of bacteria was grown by inoculating CFA agar plates with 100 l of the thawed frozen suspension and incubating the plates at 35 to 37°C for 18 h. The lawn was harvested in sterile PBS; based on optical density at 600 nm, the concentration of bacterial cells was adjusted to give the appropriate number of CFU per ml, and then 1 ml was diluted into CeraVacx and administered as doses as above.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome these side effects of strain E1392/75-2A, defined deletion mutations were introduced into the aroC gene required for biosynthesis of aromatic amino acids and the ompC and ompF genes that code for outer membrane porins. The resulting strain, PTL003, was tested in human volunteers and found to be safe and immunogenic (21,42). Based on this successful approach we are continuing to develop a vaccine that protects against a diverse range of ETEC strains, by raising an immune response to a number of CS antigens (CFA/I and CS1 to CS6), as well as to LTB.…”
mentioning
confidence: 99%